Pengaruh kualitas tidur terhadap efektivitas latihan fisik pada atlet futsal tim halus kasar kota jambi - Arrohman; Reno Saputra; Muhammad Arian Purnama; Muhammad Sukri; Mohd Adrizal; Ely Yuliawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the impact of sleep quality on the effectiveness of athletes’ training. Sleep quality is an important factor that plays a role in physical recovery, performance improvement, and injury prevention in athletes. The research method used is a quantitative  with a correlational design. This study was conducted in Jambi City with futsal athletes from the Halus Kasar FC team as the research subjects. Data were collected through a sleep quality questionnaire and observation of training effectiveness, which includes endurance, strength, speed, and agility. The data analysis technique used statistical correlation tests to determine the relationship between the two variables. The results showed that there is a significant relationship between sleep quality and the effectiveness of training in futsal athletes of the Halus Kasar FC team. Athletes with good sleep quality tend to have better training performance compared to those with poor sleep quality. Therefore, good sleep quality is very important to support the improvement of performance and training effectiveness of futsal athletes in the Halus Kasar FC team.